THE INFLUENCE OF E-WOM AND DESTINATION IMAGE ON VISIT DECISION IN THE MUSEUM NASIONAL (MUSEUM GAJAH) Jakarta - Najogi, Gorbi (International Humanities and Applied Science Journal, 2020)
The study aims to examine the influence of e-wom and destination Image on visit decision in the Museum Nasional (Museum Gajah) Jakarta. The respondents of this research are public people in Jakarta. This research survey conducted on 135 respondents by using quantitative approach. SEM-PLS had been used for data analysis. The result of this research stated that the coefficient of determination is 0.404, which means the percentage contribution of independent variables (e-wom and destination image) to the dependent variable (visit decision) is 40.4%. The remaining 59.6% is influenced or explained by other variable not included in this research model. The result of this study showed that e-wom and destination image has been significantly influenced for visit decision in museum nasional (museum gajah).